ANALISIS PASAR UANG PADA MODEL MUNDELL-FLEMING PADA PEREKONOMIAN INDONESIA (TAHUN 2010 - 2017) - Martin Luter Purba (LP2MTBM MAKARIOZ, 2018)
The Indonesian economy at this time is inseparable from the economic crisis that occurred in the international market. The government as a fiscal policy maker and Bank Indonesia as a monetary policy maker must be able to take appropriate policies to safeguard economic conditions if there is economic pressure from outside. Money market analysis to discuss the relationship between the interest rate and the level of income that appears on the money market. This study uses quarterly data from 2010-2017, using the two-stage least square simultaneous equation model. The results of this study show that domestic interest rates and inflation do not have a significant effect on changes in Indonesia's GDP, the money supply has an impact on Indonesia's GDP per capita increase, inflation expectations have no effect on changes in Indonesia's GDP, the money supply has an effect on increasing levels Domestic interest and the FED (Federal Reserve System) interest rate influence the decline in domestic interest rates.